PENGARUH SALES PROMOTION DAN PUBLISITAS TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA DEALER YAMAHA JG PALIMANAN CIREBON - Muhammad Ilham Nugraha; Lina Budiarti (CV. ADIBA AISHA AMIRA, 2024)
The development of the world's business is currently running fast, which makes competition increasingly fierce, especially in the automotive sector. Based on observations, the Yamaha JG Palimanan Cirebon Dealer has carried out sales promotion and publicity. This study aims to examine the influence of sales promotion and publicity partially and simultaneously on purchasing decisions. This research is a research with a quantitative approach that is carried out by distributing questionnaires to 100 respondents from consumers in Cirebon who have made purchases and know Yamaha JG Palimanan Cirebon Dealers. This research at Yamaha JG Palimanan Dealer Cirebon in January 2023 - June 2023 using a purposive sampling technique. Data analysis using multiple linear regression analysis. The results of testing the hypothesis partially, sales promotion has a positive and significant effect on purchasing decisions, then publicity has a positive and significant effect on purchasing decisions. The results of hypothesis testing simultaneously show that sales promotion and publicity have a positive and significant effect on purchasing decisions. There is an influence of sales promotion and publicity on purchasing decisions of 59,1% and the remaining 40,9% is influenced by other factors not discussed in this study. The results of this study can be concluded that sales promotion and publicity influence purchasing decisions at Yamaha Dealers JG Palimanna Cirebon